ANALISIS USAHATANI PORANG (Amorphophalus muelleri) DI KECAMATAN MANCAK, KABUPATEN SERANG, PROVINSI BANTEN - Rahayuningsih, Yunia (Jurnal Kebijakan Pembangunan Daerah, 2021)
The porang plant has a potential high economic value as a source of regional income and an export commodity. However, one of the biggest obstacles to porang exports lies in the limited supply of raw materials. In Mancak Subdistrict, Serang Regency, porang has been widely cultivated, but there are still many farmers who are hesitant to plant large amounts of porang. Therefore, this study aims to analyze the porang farming business so that its efficiency and feasibility values ​​are known. The research was conducted in April-May 2021 in Mancak District, Serang Regency, Banten Province. The research method used a qualitative descriptive approach with data collection techniques through interviews and literature study. Furthermore, the data were analyzed by using the R/C Ratio formula. The results showed that porang farming in Mancak Subdistrict, Serang Regency is efficient and feasible to be developed with an R/C Ratio of 3.72, which means that every 1 rupiah of farmer expenditure for porang farming will get 3.72 rupiahs of revenue.